2018
DOI: 10.1021/acs.cgd.7b01436
|View full text |Cite
|
Sign up to set email alerts
|

Opening Pandora’s Box: Chirality, Polymorphism, and Stoichiometric Diversity in Flurbiprofen/Proline Cocrystals

Abstract: Proline has been widely used for various cocrystallization applications, including pharmaceutical cocrystals. Combining enantiopure and racemic flurbiprofen and proline, we discovered 18 new crystal structures. Liquid-assisted grinding proved highly efficient to explore all the variety of crystal forms. A unique combination of state-of-the-art characterization techniques, comprising variable temperature in situ X-ray diffraction and in situ ball-milling, along with other physicochemical methods and density fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 60 publications
3
43
0
Order By: Relevance
“…The melting temperatures of cocrystals for comparison were obtained by different authors under different conditions (different heating rates and, sometimes, some authors give melting temperatures as onset values, and others as a peak on the DSC curves). In the case of [R-flurbiprofen + dl-proline], where the data was obtained by Tumanova et al (2018a), the melting points are within experimental errors.…”
Section: Comparative Analysis Of Melting Points Of Co-crystals Havingmentioning
confidence: 60%
“…The melting temperatures of cocrystals for comparison were obtained by different authors under different conditions (different heating rates and, sometimes, some authors give melting temperatures as onset values, and others as a peak on the DSC curves). In the case of [R-flurbiprofen + dl-proline], where the data was obtained by Tumanova et al (2018a), the melting points are within experimental errors.…”
Section: Comparative Analysis Of Melting Points Of Co-crystals Havingmentioning
confidence: 60%
“…In combination with flurbiprofen, proline proved to be a potent coformer, resulting in 18 different modifications (29 entries in Table S1). In Table S1, there are 24 entries of rare earth metal complexes of the types [M 2 (H 2 O) 6 (Pro) 5 ](ClO 4 ) 6 (18 structures) and [M(H 2 O) 4 (Pro) 2 ]Cl 3 (6 structures), containing unidentate and bridging bidentate proline zwitterions as ligands. Although the selectivity in the diastereomer ratio of the pyramidalization angles dr( θ ) = 13:11 is only small, the − ψ /+ ψ separated diastereomer ratios dr( θ ) − ψ = 13:2 and dr( θ ) +ψ = 8:1 demonstrate impressively the control of the pyramidalization of the carboxylic group by the − ψ and + ψ conformation in the second step of the chirality chain.…”
Section: Special Pointsmentioning
confidence: 99%
“…In combination with flurbiprofen, proline proved to be a potent coformer, resulting in 18 different modifications (29 entries in Table S1). 8 In Table S1…”
Section: Prolinementioning
confidence: 99%
“…Tumanova et al conducted a study on the ability of co-crystal formation between flurbiprofen and l -proline using the LAG method with five different solvents, i.e., methanol, ethanol, isopropanol, acetonitrile, and water; both compounds are soluble in methanol and ethanol; only flurbiprofen is soluble in isopropanol and acetonitrile, and only l -proline is soluble in water. This study showed that the choice of the solvent used for the LAG method is a factor that can affect the rate of reaction and the reaction pathway, as five co-crystal structures were found with different types of supramolecular synthon [ 86 ]. A similar thing was observed in the formation of co-crystals between naproxen and l -proline using the LAG method with five different solvents by Tilborg et al [ 87 ].…”
Section: Amino Acids As Co-formersmentioning
confidence: 99%